Validation of supervisor support scale and work-life balance checklist in Malay Language among Malaysian working mothers - Hamzah, Hazalizah; Ramlee, Fatanah; Panatik, Siti Aisyah; Chee-Seng, Tan; Jalil, Nurul Iman Abdul; Zulkifli, Syara Shazanna (Intelektual Pustaka Media Utama, 2024)
Working mothers burdened with work and household responsibilities face challenges with work-life balance, which could be empowered through supervisor support in the workplace. Therefore, it is vital to identify the impact of supervisor support on working mothers’ work-life balance. However, available instruments to measure both constructs for the Malay-speaking Malaysian population are dearth. This study assessed the psychometric properties of the Malay version of the supervisor support scale (SS-Malay) and work-life balance checklist (WLB-Malay) and investigated the relationship between these variables among Malaysian working mothers. Using purposive sampling, 200 working mothers (M=38.80, SD=8.43) for the pilot study and 275 working mothers (M=38.33, SD=7.86) for the actual study completed either an online or printed survey consisting of demographic information, the supervisor support scale, and the work-life balance checklist. Exploratory factor analysis conducted on the pilot study data reported a two-factor structure for WLB-Malay and one factor for SS-Malay. Similarly, confirmatory factor analysis confirmed the unidimensional factor of SS-Malay, and two factors of WLB-Malay: concerned about work, and self. Reliability was established with alpha, omega, and composite reliability values of more than .70. Discriminant validity was established with correlation values of less than .90, and concurrent validity was established with significant moderation positive association between constructs. Structural equation modelling reported a satisfactory model fit for both scales and identified a positive impact of supervisor support on work-life balance among Malaysian working mothers. Accordingly, both WLB-Malay and SS-Malay are culturally fit for Malaysian working mothers.